2018
DOI: 10.20517/2394-5079.2017.51
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of outcomes between laparoscopic vs. open liver resection for intermediate stage hepatocellular carcinoma

Abstract: Aim: The Barcelona Clinic Liver Score (BCLC) currently limits hepatic resection only for small, solitary tumors measuring 2-3 cm with no signs of portal hypertension (PHT) or macrovascular invasion. The aim of this study was to show the benefit of surgical resection, and to compare the peri-operative and long-term outcomes between laparoscopic liver resection (LLR) and open liver resection (OLR) for hepatocellular carcinoma (HCC) classified as intermediate stage (B) under BCLC. Methods: From 2004 to 2013, 49 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…As for LLR per se, despite comparable short-term outcomes, it is still under investigation whether the laparoscopic approach is justified for HCC in terms of the long-term oncologic results, such as resection margin, recurrence rates and survival. Several studies reported promising perioperative results without compromise in the oncologic outcomes for LLR [ 3 , 7 , 10 , 11 , 12 , 13 ]. However, the heterogeneity of the patient population, disease status, extent of liver resection, and procedural type complicated the assessment for LLR.…”
Section: Introductionmentioning
confidence: 99%
“…As for LLR per se, despite comparable short-term outcomes, it is still under investigation whether the laparoscopic approach is justified for HCC in terms of the long-term oncologic results, such as resection margin, recurrence rates and survival. Several studies reported promising perioperative results without compromise in the oncologic outcomes for LLR [ 3 , 7 , 10 , 11 , 12 , 13 ]. However, the heterogeneity of the patient population, disease status, extent of liver resection, and procedural type complicated the assessment for LLR.…”
Section: Introductionmentioning
confidence: 99%